(untitled) (AACINI - International Journal of Industrial Engineering, 2020)
The objective of this paper was to take knowledge of changes in social and individual habits experienced by students during the virtual classes and their expectations at the time of taking the final evaluations with distance modality in times of pandemic. An online survey was conducted with 38 Industrial Engineering students of the Faculty of Agricultural Sciences at the National University of the Northeast, from 19 to 37 years old (34 % women, 66 % men). Ninety two percent of students changed their study habits, related to schedules, having to study on their own, returning to their homes of origin, sharing the computer with family members, not having fixed schedules in some subjects, among other things. In addition, 16 % considered that their level of understanding of the topics improved, whereas 37 % were able to better organize their time during the purely virtual classes. Regarding the possibility of taking a virtual final exam, it was observed anxiety in 68 % of the respondents, added to conditions of interest. In summary, students have experienced changes during the virtual course, having to organize their time, their study space, depending on external factors, such as connectivity and availability of technological devices, the change of place of residence with the factors involved. It is noted that, at the time of the survey, they had not yet had virtual final exams and were mainly eager to pass that moment.